Analysis of onion production under different irrigation regimes - Abreu, Tânia A. dos Santos; Millar, Augustin A.; Choudhury, Eliane Nogueira; Choudhury, Mohammad M. (Pesquisa Agropecuaria Brasileira, 2014)
This work was conducted to study the effect of five water regimes on the onion production and bulb mean weight of variety 'Amarela Chata das Canárias'. The treatments consisted in irrigating when soil water was depleted to -0.1, -05, -1, -2 and -4 bars levels of matric potential. At harvest, production and bulb mean weight were obtained. For production, significative difference was found between the treatments at 0.05 level. The productions of treatments -0.5, -1, -2 and -4 bays did not differ statistically. The greatest production was obtained for irrigation treatment -0,1 bar, which was 81.7% higher than the production mean of the other treatment. The bulb mean weight decreased with decreasing soil matric potential (increasing suction). The mean weights were 130, 72, 63, 58 and 52.5 grams for the treatments watered at -0.1, -0,5. -1, -2 and -4 bars. The commercial productions with bulb mean weight in the range of 50- 150 grams were 45, 70, 65, 60 and 50% of total production, respectively, for the same water regimes.